2005
DOI: 10.7202/051352ar
|View full text |Cite
|
Sign up to set email alerts
|

Staying the Decline in Union Membership : Union Organizing in Ontario, 1985-1999

Abstract: Les syndicats en Ontario, et au Canada en général, ont dû faire face à une crise d'adhésion. Cette crise est le résultat de la restructuration économique, des changements politiques et législatifs, et des employeurs enhardis dans leur opposition aux syndicats. Les taux de syndicalisation sont en déclin ou stagnants et il y a des bas taux de syndicalisation dans des secteurs croissants de l'économie, plus particulièrement dans les industries de services du secteur privé. Cette étude, centrée sur l'Ontario, exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 8 publications
3
18
0
Order By: Relevance
“…Our interviews corroborated other studies showing that women are actively seeking union representation (Bronfenbrenner and Juravich, 1998;Yates, 2000). At Pluto, women were very active in the organizing drive.…”
Section: The Organizing Drivesupporting
confidence: 89%
“…Our interviews corroborated other studies showing that women are actively seeking union representation (Bronfenbrenner and Juravich, 1998;Yates, 2000). At Pluto, women were very active in the organizing drive.…”
Section: The Organizing Drivesupporting
confidence: 89%
“…The Canadian context has been deemed relatively labour‐friendly in comparison with other Anglo‐speaking countries (Godard, ; Rose & Chaison, ), but maintains a statutory union recognition system that tends to encourage adversarial contest between managers and the union (Wood & Godard, ). Unlike drastic declines in union density in the United States and United Kingdom over the past few decades, Canada's union density rate has experienced a much less significant decline and currently sits at approximately 30% (Yates, ). Furthermore, Canadian legislation restricts employer communication with employees during the organizing drive to neutral, non‐threatening, and factual information.…”
Section: Methodsmentioning
confidence: 99%
“…The literature on expected management reprisal has suggested that other factors (i.e., union tactics; Bronfenbrenner & Hickey, 2004;Yates, 2000) may be more important to union organizing drives or voting propensity and also that strong anti-union tactics can backfire by angering employees (Bronfenbrenner, 1997;Fiorito, 2001). Specifically Godard (2011) found a strong positive association with voting propensity when a negative management response was deemed 'somewhat likely' as opposed to 'unsure.'…”
Section: Factors Related To Union Voting Propensitymentioning
confidence: 99%